Potential preventive effects of selected traditional Chinese medicine as adjuvant therapy on hypertensive heart disease progression by replenishing qi and activating blood circulation: a systematic review and meta-analysis of clinical trials - Hui, Jiaqi; Wang, Ya; Xu, Fengqin; Zhao, Junnan (Frontiers in Pharmacology, 2025)
ObjectiveHypertension remained an important public health problem with high morbidity and mortality and was emerging as a risk factor for future heart failure. The transition from hypertension to hypertensive heart disease (HHD) and heart failure grew progressively with time. Traditional Chinese medicine (TCM) has a history of several thousand years, where selected TCM for replenishing qi and activating blood circulation provides an alternative treatment for HHD.MethodsAn extensive literature search was conducted across eight electronic databases from their inception until 8 September 2023, to evaluate the potential preventive effects of selected TCM as an adjuvant therapy on the progression of HHD. The outcome measures included blood pressure and indicators of cardiac structure and function under cardiac ultrasound. The mean difference (MD) and 95% confidence interval (CI) were used to determine continuous outcomes. Risk ratio (RR) with 95% confidence interval (CI) was used to determine dichotomous outcomes. The information about the overall certainty of the evidence from studies was presented according to specific outcomes using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) Guideline Development Tool (GDT) online software.ResultsTwenty-one randomized controlled trials (RCTs) involving 2, 055 participants were included. Meta-analyses favored integrated Chinese botanical drugs and Western medicine on blood pressure, New York Heart Association classification, left ventricular ejection fraction, transmitral peak early diastolic velocity/peak late diastolic velocity ratio, left ventricular internal diameters, left ventricular mass index, interventricular septum thickness in diastole, and B-type natriuretic peptide compared with Western medicine alone. Results on cardiac output should be interpreted with caution due to sample size limitations. No severe adverse events were identified. Most of the Chinese botanical drugs originated from classical TCM formulas. The dosage form of Chinese botanical drugs was oral. Salvia miltiorrhiza Bunge (Danshen), Oreocome striata (DC.) Pimenov & Kljuykov (Chuanxiong), Pueraria montana var. lobata (Willd.) Maesen & S.M.Almeida ex Sanjappa & Predeep (Gegen), Astragalus mongholicus Bunge (Huangqi), and Typha angustifolia L. (Puhuang) were the top 5 Chinese botanical drugs, which might be associated with replenishing qi and activating blood circulation.ConclusionSelected TCM had the potential to be effective as an adjuvant therapy for alleviating adverse left ventricular remodeling and improving cardiac function after HHD, and therapy of replenishing qi and activating blood circulation may serve as a potential reference for treatment. To better assess Chinese botanical drugs’ preventative effects, more long-term, high-quality RCTs are still necessary.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/#myprospero, identifier CRD42022346030.